Comparison of efficacy of single-port versus conventional laparoscopic treatment for uterine leiomyoma: a latest meta-analysis - Li, Yanhui; Liu, Rui; Li, Xue (Frontiers in Oncology, 2023)
Single-port laparoscopy has been proposed as an ideal surgical method for the treatment of uterine leiomyoma. It can effectively remove the lesion, reduce the loss of hemoglobin, and has superior cosmetic effects. Therefore, we searched relevant studies and conducted a meta-analysis to evaluate the effect of single-port laparoscopy on myoma resection, hemoglobin loss, and scar beauty compared to conventional laparoscopy.We systematically searched PubMed, EMBASE, scope, Cochrane, CNKI, and other databases to find randomized controlled studies on the efficacy of single-port laparoscopy and traditional laparoscopy for meta-analysis. The main outcomes of our study were the duration of surgery, the reduction of hemoglobin, and the cosmetic effect of the postoperative scar. The effect model was selected according to heterogeneity (random effect model or fixed effect model), and the relevant sensitivity analysis and publication bias test were performed.We searched a total of 501 related literature articles and finally included 19 studies involving 21 researchers. Comparison of single-port laparoscopic myomectomy with traditional surgery: Operation time had no significant difference (Standardized Mean Difference [SMD]: 0.13, 95% Confidence interval (CI), -0.04 to 0.30; I²=74%; P = 0.14); The reduction of hemoglobin is lower ([SMD]: -0.04; 95% CI, -0.23 to 0.14; I²=71%; P = 0.65), and the cosmetic effect of postoperative scar is more satisfactory ([SMD]: 0.42, 95% CI: 0.02 to 0.83; I²=72%, P= 0.04). There was no significant difference in conversion rate, postoperative pain, blood loss, postoperative gastrointestinal recovery time, or length of hospital stay.Compared with traditional laparoscopy, the operation time of the treatment of uterine leiomyoma by single-port laparoscopy is not extended, the reduction of hemoglobin is less, and the cosmetic effect of the scar is better. Therefore, single-port laparoscopy is superior to traditional surgery in the treatment of uterine leiomyoma.